Penerapan Metode SDLC Model Waterfall Dalam Rancang Bangun Aplikasi Monitoring Stok Bahan Baku Produksi Di UMKM Salad Mertua - Bayu Pratama, Eri; Mulya Fahriansyah , Teddy; Hendini, Ade (LPPM Universitas Bina Sarana Informatika, 2023)
The purpose of the conducted research is to create an application for monitoring raw material stock in production at UMKM Salad Mertua, ensuring control over raw material inventory data. The application is developed as a website with three levels of user access (owner, warehouse department, and production department), each tailored to specific data processing procedures required for their respective roles. The application's design is structured using the waterfall software development method, where the database design is depicted in entity relationship diagrams (ERD) and logical record structures (LRS). The programming language utilized for the application's development is PHP, connected to a MySQL database. The outcome of this research is a monitoring application providing information on the required stock of raw materials for salad production in UMKM Salad Mertua, ensuring that the procurement needs and quality of raw materials are maintained according to the application of the SDLC method with the waterfall model.